2007
DOI: 10.1002/adic.200790074
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Status and the Effect of Soil Erosion on Trace Elements in Nanka and Oba Towns of Anambra State, Nigeria

Abstract: Iodine Deficiency Disorders (IDD) is common in all populations. Iodine and other trace elements naturally occur in the soil but erosion leaches off these elements from the soil. This results in a continued loss of trace elements from the soil. In the present study, the levels of iodine, selenium, zinc and lead in the environment (measured in soil, bitter leaves (Vernonia amygdalina), cassava roots (mannihot utilissima, staple food in Nigeria), and drinking water) and urinary iodine from school children (n=200)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…We found no significant difference in selenium level between rural preeclamptic pregnant women and the urban group (p > 0.05). This finding is in line with previously conducted study in Nigeria [32].However, another study in other part of Nigeria found statistically significant difference for selenium between both communities [33].As per as we know,this is the first study which attempted to evaluate theconcentrationof selenium in terms of the severity of the disease. For this reason, we further categorized the preeclampsia patients in mild and severe classes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found no significant difference in selenium level between rural preeclamptic pregnant women and the urban group (p > 0.05). This finding is in line with previously conducted study in Nigeria [32].However, another study in other part of Nigeria found statistically significant difference for selenium between both communities [33].As per as we know,this is the first study which attempted to evaluate theconcentrationof selenium in terms of the severity of the disease. For this reason, we further categorized the preeclampsia patients in mild and severe classes.…”
Section: Discussionsupporting
confidence: 92%
“…The main reason for decreased selenium in these patients may be due to transfer of selenium from maternal blood to the tissues of the growing fetus. [32]. This could also due to poor absorption of selenium from the gastrointestinal tract, or inadequate renal reabsorption leading toenhanced glomerular filtration rate in preeclamptic pregnant women [30].…”
Section: Discussionmentioning
confidence: 98%
“…It not only affects the human direct intake of iodine from water but also influences the iodine content of food produced regionally with positive correlation with local population total goiter rate and median urinary iodine excretion [37]. Our data on median regional iodine concentration in drinking water ranged from 2.4 and 16.2 mcg/ l, in line with some previous reports, but well below other West Africa results [6,38]. Its current contribute to total iodine intake of SAC in Guinea-Bissau is unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic occupational and environmental exposure to Pb has lead to increase in serum Pb level which causes anaemia, peripheral neuropathy and venal tubular dysfunction (Olife et al, 2007). Also, there is strong evidence that hexavalent Cr causes cancer in laboratory animals when it is consumed in drinking water.…”
Section: Resultsmentioning
confidence: 99%